2001
DOI: 10.2134/agronj2001.932458x
|View full text |Cite
|
Sign up to set email alerts
|

Interseeding Kura Clover and Birdsfoot Trefoil into Existing Cool‐Season Grass Pastures

Abstract: Legumes in cool‐season grass pastures can improve productivity and quality. In May of 1997 and 1998, a split‐split plot field experiment with six replications was planted in Morris, MN to evaluate the effect of sod suppression, planting method, and legume species on establishment of legumes into existing cool‐season grass pastures and to evaluate kura clover (Trifolium ambiguum Bieb.) and birdsfoot trefoil (Lotus corniculatus L.) as potential species for interseeding in the North Central region. Whole‐plot sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Seedling density of birdsfoot trefoil and white clover seemed unaffected by pest protection or tall fescue suppression. In contrast, Cuomo et al [12] found that suppression by glyphosate of cool-season grasses enabled much greater success in obtaining legume stands that included alfalfa, birdsfoot trefoil, red clover, and kura clover (Trifolium ambiguum M. Bieb.).…”
Section: Experiments 1: Pest Control and Grass Suppressionmentioning
confidence: 95%
See 1 more Smart Citation
“…Seedling density of birdsfoot trefoil and white clover seemed unaffected by pest protection or tall fescue suppression. In contrast, Cuomo et al [12] found that suppression by glyphosate of cool-season grasses enabled much greater success in obtaining legume stands that included alfalfa, birdsfoot trefoil, red clover, and kura clover (Trifolium ambiguum M. Bieb.).…”
Section: Experiments 1: Pest Control and Grass Suppressionmentioning
confidence: 95%
“…Approaches to improving legume establishment in tall fescue are numerous and include no-till drilling of legumes into tall fescue pasture [11]; controlling grass competition with herbicides [12], mowing, or grazing [13]; limiting N fertilization [14]; and planting pastures with different row orientations [15]. Although considerable research has been conducted on legume establishment, little progress has been made to address many of the problems, such as disease, insect damage, heat and/or water stress, and poor seedling vigor [2].…”
Section: Introductionmentioning
confidence: 99%
“…The requirements for ecological conformity of herbicide application necessitate searching for herbicides having significantly good selectivity and a high effect on the weeds in the contemporary ecological conditions [CUOMO, 2001;NIKOLOVA, 2003] .…”
Section: Introductionmentioning
confidence: 99%
“…Whether pure sown or in mixture with grasses, competition for light from weeds and grasses will probably limit the establishment of legumes in pastures (Lanini et al, 1991;Simmons et al, 1995). It has been reported that legume inter-seeding was most successful when competition from grasses is reduced through herbicide application (Groya and Sheaffer, 1981;Cuomo et al, 2001) or by cutting swards to low heights before seeding legumes (Taylor and Allinson, 1983). The observation of growth and morphological plasticity of legume seedlings under different light conditions is necessary for the management before seeding.…”
Section: Introductionmentioning
confidence: 99%